Perbandingan Defisit Neurologis Pada Pasien Stroke Berdasarkan Letak Lesi Pada Hemisfer: Literature Review - Nabila, Ovilia; Rukmi, Dwi Kartika (Jurnal Keperawatan Notokusumo, 2021)
Background: Stroke is one of the vascular injuries with the highest incidence in the world. Stroke can cause neurological deficits in the form of disturbances in movement, sensation, cognitive function, and emotions that are mild or severe depending on the location of the damage, how large the area is experiencing inadequate perfusion, and depending on the function of the damaged area. Objective: To compare neurological deficits in stroke patients based on the location of the lesions in the hemisphere. Methods: We conducted a systematic literature review on articles published in the 2011-2021 period. Data was collected from three databases (Google Scholar, PubMed, and Portal Garuda), using the keywords “Neurologic Deficit”,“Stroke”, “Hemisphere”. Results: 10 articles were included in the review. The results obtained: (1) The incidence of decreased cognitive function is more common in left hemispheric stroke patients, (2) Unilateral neglection is more common in right hemispheric stroke patients. (3) there is no difference between balance and level of ability to perform daily activities. (4) the incidence of post-stroke depression is suspected to be higher in patients with left hemisphere lesion stroke and is one of the causes of decreased quality of life in post-stroke patients. Conclusion: Specialization of hemispheric function affects the severity of neurological deficits in stroke patients.